1986
DOI: 10.1111/j.1432-1033.1986.tb09537.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic antigens of Pseudomonas aeruginosa

Abstract: Lipopolysaccharides from Pseudomonas aeruginosa 01 (Lhnyi classification), 0 3 (Habs classification), 0 1 3 and 014 (Wokatsch classification), and strain NCTC 8505, which is also related to serogroup 0 3 (Habs), have structurally similar 0-specific polysaccharide chains built up of tetrasaccharide repeating units involving L-rhamnose (Rha), 2-acetamido-2-deoxy-~-glucose (GlcNAc), 2-acetamido-2-deoxy-~-galacturonic acid (GalNAcA), and a di-N-acyl derivative of bacillosamine (BacN): 2,4-diacetamido-2,4,6-trideox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…The position of the signals for C-5 and C-7 in the region of 46 -54 ppm showed that these carbons carried nitrogen, and the chemical shifts of the signals for C-3 (34.8 ppm) and C-9 (16.2-16.3 ppm) indicated that these carbons entered the deoxy units. The position of the signals of xylose in the spectra of [1][2][3] were in good agreement with the data for methyl B-D-xylopyranoside [24], and hence this monosaccharide occupied the non-reducing terminus of the oligosaccharides. The use of the 13C nuclear magnetic resonance data for the determination of the mode of glycosidation and substitution by 0-acyl and N-acyl groups in I -3 was described above.…”
Section: Interpretation Of 3c Nuclear Magnetic Resonance Spectrasupporting
confidence: 75%
See 1 more Smart Citation
“…The position of the signals for C-5 and C-7 in the region of 46 -54 ppm showed that these carbons carried nitrogen, and the chemical shifts of the signals for C-3 (34.8 ppm) and C-9 (16.2-16.3 ppm) indicated that these carbons entered the deoxy units. The position of the signals of xylose in the spectra of [1][2][3] were in good agreement with the data for methyl B-D-xylopyranoside [24], and hence this monosaccharide occupied the non-reducing terminus of the oligosaccharides. The use of the 13C nuclear magnetic resonance data for the determination of the mode of glycosidation and substitution by 0-acyl and N-acyl groups in I -3 was described above.…”
Section: Interpretation Of 3c Nuclear Magnetic Resonance Spectrasupporting
confidence: 75%
“…Investigation of the lipopolysaccharides of an opportunistic bacterial pathogen P. aeruginosa showed many [2, 81, acetamidino [5, 6, 91, (R)- [7] and (S)-3-hydroxybutyryl [3] groups.…”
Section: +~) -D -X~~~-(~~+~) -D -F~c N a C -(~~+~) -P S~~n A C~n F~-(~mentioning
confidence: 99%
“…The situation involving two D (or two L) sugars would result in a large upfield shift of C2 (-1.2) and a minor shift of C4 (-O.l), whereas the opposite situation (i.e. either L-D or D-L substitution) would result in two large negative p-effect shifts, as can be seen for D-QuiNAc4NAc substituted by L-GalNAcA [24]. Thus, as the substituting sugar is a-D-GalNAcA and only C2 possesses a large negative shift, the QuiNAc4NAc residue must also be D configurated.…”
Section: Resultsmentioning
confidence: 96%
“…By using two-dimensional-NMR spectrometric techniques it was possible to confirm both aminouronic acids as a-GalNAcA (residues A and B, see (6 76.83), with reference to the specific unsubstituted residues [24], were indicative of a repeating unit containing two 4-substituted GalNAcA residues and one 3-substituted QuiNAc4NAc residue. The absolute configuration of the QuiNAc4NAc residue was identified by comparing the "C-NMR p-effects of substitution of this residue [C2 -ve p-effect (-2.41), C4 +ve p-effect (+0.05)] with those for the theoretical residue, a 3-substituted residue possessing the gluco configuration and substituted by a sugar possessing the a-D configuration [25], with respect to unsubstituted QuiNAc4NAc [24]. The situation involving two D (or two L) sugars would result in a large upfield shift of C2 (-1.2) and a minor shift of C4 (-O.l), whereas the opposite situation (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation